The Description of The Physiological Response and Milk Production of Etawah Crossbreed (PE) Goats Injected With The Oxytocin Hormone - Dzarnisa Dzarnisa; Cut Intan Novita; Didy Rachmadi (Faculty of Animal Science, Universitas Brawijaya, 2021)
This study aimed to know the physiological response and milk production of Etawah Crossbreed (PE) goat injected with the hormone oxytocin. The mechanism of action of the oxytocin hormone in the body will suppress the production of the cortisol hormone, which causes livestock stress. For now, there are not many publications about the induction of oxytocin hormone in PE goats. In this research, the researchers will provide the latest information. The research material is 18 lactation PE goats divided into 2 groups, namely control and hormone treatment. This research is in the form of an experimental research design with a control group post-test only design. The design used is an independent t-test. Hormone injection is carried out intramuscular, as much as 1 ml with a dose of 10 IU. The parameters measured were milk production (ml), heart rate (times/minutes), and respiration frequency (times/minutes). Oxytocin injection had no significant effect (P>0.05). Still, it tended to increase the milk production of PE goats in the morning and evening with total milk production of 1103.65±145.72ml compared to without injection of 884.38±90.49ml in 1 day. Similarly, the injection of the hormone oxytocin did not affect the frequency of respiration in the morning and evening. However, it was different from the PE goats heart rate, which had a significant effect (P<0.01) in the morning. On the other side, there was no significant effect (P>0.05) in the afternoon. The indicators of stress in dairy cattle are respiration frequency and heart rate outside normal limits, affecting milk production. This study concluded that the induction of the oxytocin hormone did not affect milk production, and the cattle did not experience stress because the heart rate and respiration frequency were in the normal range due to the injection of the oxytocin hormone.